Shelf-Life Extension of Refrigerated Turbot (Scophthalmus maximus) by Using Weakly Acidic Electrolyzed Water and Active Coatings Containing Daphnetin Emulsions - Liu, Wenru; Wang, Qi; Mei, Jun; Xie, Jing (Frontiers in Nutrition, 2021)
This research was to investigate the effect of weakly acidic electrolytic water (WAEW) treatments combining with the locust bean gum (LBG) and sodium alginate (SA) active coatings containing daphnetin emulsions on microbiological, physicochemical, and sensory changes of turbot (Scophthalmus maximus) during refrigerated storage at 4 °C for 24 days. Results showed that WAEW together with LBG-SA coatings containing daphnetin emulsions treatments could significantly lower the total viable count (TVC), H2S-producing bacteria, Pseudomonas spp. and psychrotrophic bacteria counts, and inhibit the productions of off-flavor compounds including the total volatile basic nitrogen (TVB-N), inosine (HxR) and hypoxanthine (Hx). Further, the treatments also prevented textural deterioration, delayed water migration and had higher organoleptic evaluation results. Therefore, WAEW together with LBG-SA coatings containing daphnetin emulsions treatments had the potential to improve the quality of turbot during refrigerated storage.